Successful purification of DNA from PFGE agarose plugs for whole genome sequencing - Katja Strašek Smrdel; Andraž Celar Šturm; Tina Triglav; Mateja Pirš (Acta Biologica Slovenica)
Whole-genome sequencing (WGS) has replaced Pulsed-field gel electrophoresis (PFGE)-based bacterial genotyping as the reference genotyping method. We investigated the suitability of purified genomic DNA extracted from PFGE agarose plugs stored in a laboratory collection for WGS in cases where bacterial isolates are no longer available. Our study has shown that bacterial WGS can be successfully performed on DNA extracted from PFGE agarose plugs.